Solid state electrical conductivity properties of copper complexes of novel oxime compounds containing oxolane ring - Aydogdu, Y; Yakuphanoğlu, Fahrettin; Aydogdu, A; Tas, E; Cukurovali, A (Elsevier Science Bv, 2003)
In this study, a novel dioxime having the 1,3-oxolane group, 1,2-dihydroxyimino-3,7-diaza-9,10-O-cyclohexylidenedecane ((LH2)-H-1) and 9,10,bis(hydroxyimino)-4-8,11,15-tetraaza-1,2,17,18-O-dibenzaloctadecane ((LH2)-H-2), were synthesised from 1,2-O-benzal-4-aza-7-aminoheptane, which was prepared from a reaction of 1-choloro-2,3-O-benzalpropane and dichlorogloxime. The electrical properties of complexes of those ligands with Cu(II) salts were investigated and obtained results were analyzed. It was seen that these complexes had semiconducting properties. The activation energies (E-a) were calculated for the complexes by using the Arrhenius plot. Thermal probe measurement indicated that these complexes had an n-type electrical conductivity. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: complex; 1,3-dioxime; transition metals; semiconductor; activation energy